(untitled) (Communications in Mathematical Research, 2019)
This paper deals with the Hyers-Ulam stability of the nonhomogeneous linear dynamic equation x^Δ(t)-a x(t)=f(t), where aR^+. The main results can be regarded as a supplement of the stability results of the corresponding homogeneous linear dynamic equation obtained by Anderson and Onitsuka (Anderson D R, Onitsuka M. Hyers-Ulam stability of first-order homogeneous linear dynamic equations on time scales. Demonstratio Math., 2018, 51: 198–210).